(untitled) (Bangladesh Heart Journal, 2024)
Background: Hypoalbuminemia is associated with morbidity and mortality in critically ill children and is a well-recognized predictor of general surgical risk. It frequently occurs in patients with congenital heart disease (CHD). Moreover, cardiopulmonary bypass (CPB)-induces an inflammatory response, and the overall surgical stress can affect albumin concentration greatly Objective: To estimate pre-operative, per-operative and post-operative serum albumin level and to see its influence on immediate outcomes in children with congenital heart disease undergoing cardiac surgery with cardiopulmonary bypass Methods: This cross-sectional observational study was conducted in Paediatric cardiology department, BSMMU in a view to find out the influence of pre-operative, per-operative and post-operative serum albumin level on immediate outcomes in children with congenital heart disease undergoing cardiac surgery with cardiopulmonary bypass(CPB).The study included total 48 patients of CHD who underwent CPB. Patients were selected according to inclusion and exclusion criteria. Result: Mean pre-operative serum albumin was 3.5±0.9 mg/dl whereas per-operative and post-operative serum albumin was 3.3±0.7mg/dl and 3.1±0.7 mg/dl respectively.CPB time was a bit higher in study population (98.4± 29.1min) where as other outcome parameters were within normal range. Duration of hospital stay was 12.2±3.1days. 22 patient (45.8%) developed valvular regurgitation and 6 patient (12.5%) developed pericardial effusion in post-operative echocardiography. Infection was evident by positive blood culture in 7 patients (14.8%). Pre, per and post-operative hypoalbuminaemia was associated with poor outcome after CPB. Conclusion: Pre, per and post-operative hypoalbuminaemia is a prudent indicator for speculating poor immediate outcome following CPB in children with CHD. (Bangladesh Heart Journal 2024; 39(2): 121-126